PEMIKIRAN PENDIDIKAN KH. HASYIM ASY’ARI DAN TRADISIONALISME - Akmal Hawi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
K.H. Hashim Al Asy'ari was a scholar founder of Nahdlatul Ulama (NU), the biggest social organization in Indonesia. He was also the founder of boarding school of Tebuireng, East Java, and was known as a personage of the reformer of boarding schools. In addition to teaching religion in boarding school, he also taught the students to read books of general knowledge, organization, and speech. Thoughts of Hasyim Asy’ari in education more emphasis on ethics in education, although not denying some other educational aspects. In this case much influenced by his expertise in the field of Hadits, and his thoughts in the field of Sufism and fiqih in line with theology of al Asy'ari and al Maturidi. It was in line with the thoughts of al-Ghazali, more emphasis on spiritual education. And to achieve it somebody who learnt or taught must have ethics, had the manners and morals, either students or teachers themselves. K.H. Muhammad Hashim Asy'ari viewed that educators were as a party that was very important in education. For him, the teacher was a person who was capable of transmitting knowledge in addition to forming ethics and attitudes of learners. How was the substance of educational thoughts of K.H. Hasyim Asy’ari? The answer of this question will be discussed in this article.